SMAD7 Directly Converts Human Embryonic Stem Cells to Telencephalic Fate by a Default Mechanism123. (19th December 2012) - Ozair, Mohammad Zeeshan; Noggle, Scott; Warmflash, Aryeh; Krzyspiak, Joanna Ela; Brivanlou, Ali H.
Abstract Human embryonic stem cells (hESCs) provide a valuable window into the dissection of the molecular circuitry underlying the early formation of the human forebrain. However, dissection of signaling events in forebrain development using current protocols is complicated by non‐neural contamination and fluctuation of extrinsic influences. Here, we show that SMAD7, a cell‐intrinsic inhibitor of transforming growth factor‐β (TGFβ) signaling, is sufficient to directly convert pluripotent hESCs to an anterior neural fate. Time course gene expression revealed downregulation of MAPK components, and combining MEK1/2 inhibition with SMAD7‐mediated TGFβ inhibition promoted telencephalic conversion. Fibroblast growth factor‐MEK and TGFβ‐SMAD signaling maintain hESCs by promoting pluripotency genes and repressing neural genes. Our findings suggest that in the absence of these cues, pluripotent cells simply revert to a program of neural conversion. Hence, the "primed" state of hESCs requires inhibition of the "default" state of neural fate acquisition. This has parallels in amphibians, suggesting an evolutionarily conserved mechanism. STEM Cells2013;31:35–47